Analisis Laju Geokimia Penetralan Air Asam Tambang Dengan Metode Open Limestone Channel Dan Penambahan Biji Kelor - Ratmi Nurhawaisiah, Sitti; Budiman Thamsi, Alam; Wardana, Lubis (Jurnal of Mining Insight, 2023)
The environmental influence of coal mining activities is one of the changes in soil quality, air quality and surface water. Therefore, this research was carried out to find out whether mine acid water can be neutralized using a passive method by utilizing  the Lime Stone Channel system and adding moringa seeds by paying attention to variables that refer to the Constitution, namely pH (acidity), TSS (Total Suspended Solod) and heavy metal parameters of Manganese (Mn) and Iron (Fe). The research method was carried out by analyzing TSS (Total Suspended Solid) physical parameter test data, chemical parameter test data (Fe and Mn), and XRD (Limestone) data. The results of the study showed that it was known that  the Open Limestone Channel method and the addition of moringa seeds could neutralize the pH level and the benefits of moringa seeds were functional and useful for reducing or filtering the sludge contained in the samples, as well as limestone samples were useful for filtering or neutralizing the pH level in the mine acid water samples.